PERAN PEMERINTAH DAERAH KABUPATEN SIAK DALAM PENGEMBANGAN KELOMPOK SADAR WISATA BIDANG AGROWISATA DI KECAMATAN BUNGARAYA KABUPATEN SIAK TAHUN 2018 - Unggul Nugroho; Baskoro Wicaksono (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
One of the tourism potentials that has begun to be sought after in Siak Regency is nature tourism based on agrotourism in Bungaraya District. However, in the effort to develop Agro Tourism by the Tourism Awareness Group in the District of Bungaraya there were several obstacles that caused the disruption of the development of attractions. The formulation of the problem in this study are (1) What is the role of the Siak Regency Government in developing the Tourism Awareness Group in the Agro Tourism Sector in Bungaraya District in Siak Regency in 2018? (2) what are the inhibiting factors in the effort to develop agrotourism in Bungaraya Subdistrict, Siak Regency in 2018? This research aims to (1) describe the role of the Regional Government of Siak Regency in the development of tourism objects in the Bungaraya District in Siak Regency in 2018, (2) describe the inhibiting factors in the development of tourism objects in the Bungaraya District in Siak Regency in 2018. This research is a research which uses a qualitative approach with the type of qualitative descriptive research. The location of this research was carried out in the Siak Regency Tourism Office and attractions in Bungaraya District. Data collection techniques performed were through interviews and documentation. The data analysis technique used is an interactive analysis model. The results of the study concluded that the role of the Siak District Government in the development of Pokdarwis in the field of agro-tourism in the Bungaraya District of Siak Regency can be seen through its role as, motivator, facilitator, and dynamicator. In Agro-tourism development is still dominated by the role of Pokdarwis compared to the Regional government. The role of the Siak Regency Government in developing tourist objects in the Bungaraya District is influenced by internal factors such as budget constraints and inadequate human resources. While external factors such as the lack of public participation in the development of tourism objects and the low involvement of the private sector in the development of attractions. Keywords: Efforts, Tourism Development, Bungaraya Agro Tourism